The Translation Style of Old Greek Habakkuk : Methodological Advancement in Interpretative Studies of the Septuagint. - Mulroney, James A. E. (Forschungen zum Alten Testament., 2016)
In this volume, James A. E. Mulroney explains the Greek style of the Old Greek (Septuagint) book of Habakkuk. Where previous studies have focused on an interlinear model, aligning the Hebrew with the Greek text, this study looks at the Greek text in its own right. Of first importance is the notion of transformation in linguistic/translation studies: all translation involves interpretation. Therefore, the Old Greek is an interpretation of its Hebrew base text. The author offers an extended analysis of present methodological issues in the field of Septuagint studies. The study shows that the translator was not following literalism as commonly understood, but a reading tradition that is exemplified in subtle theological details of the book. The translator's personal style is seen in his use of Greek rhetoric, with most textual features representing his habit of reading in both Hebrew and Greek.